CURRENT TRENDS OF THE USE OF ECO-MATERIALS IN THE DESIGN OF LIGHT INDUSTRY PRODUCTS - Pashkevych, K. L.; Kolosnichenko, O. V.; Veklych, A. M.; Ovdіienko, Т. А. (Art and Design, 2019)
The purpose. Analysis of the basic directions of eco-design; development of classifications of eco-materials; determination of perspectives of their use in the design of the handbags. Methodology. The research is based on systematic analysis of eco-materials in clothes and in handbags, as well as on general methodology of clothes and accessories design. The methods of system-structural analysis and visual-analytical method are used at different stages of the research. Results. The basic principles of eco-design have been studied, the classification of eco-materials has been developed, the tendencies of using eco-materials in the design of handbags have been determined, the trends of fashion have been analyzed and the collection of handbags made of cork material has been created. The use of eco-materials in the design of light industry products makes it possible to obtain new aesthetic properties, thereby opening new opportunities for the development of the fashion industry. The use of eco-materials promotes for the development of new constructive techniques by the designers, for the creation of the latest technologies in fashion industry; it makes it possible to diversify the artistic solution of the costume and to improve its expressiveness. Scientific novelty. The regularities of formation of accessories collections in eco-style, as well as the basic hallmarks of style (color palette, accessories and furnishings) are determined. Practical significance. The collection of eco-style handbags with the use of cork material, based on current fashion trends, is developed.